Zoledronic acid: clinical utility and patient considerations in osteoporosis and low bone mass - Ronald C Hamdy (Dove Medical Press, 2010)
Ronald C Hamdy1,21Chair, Quillen Chair of Geriatrics and Gerontology, Quillen College of Medicine, East Tennessee State University, 2Staff Physician, Mountain Home Veterans’ Administration, Tennessee, USA Abstract: The availability of a once-a-year zoledronic acid infusion heralds a new era in the management of osteoporosis. It virtually eliminates the problem of poor compliance with orally administered bisphosphonates and, because it bypasses the gastrointestinal tract, it is not associated with gastrointestinal side effects. Zoledronic acid is effective for the treatment and prevention of postmenopausal osteoporosis, and for the treatment of osteoporosis in men, and glucocorticoid-induced osteoporosis. When administered within three months of a hip fracture, it reduces mortality and the risk of subsequent fractures. It is remarkably free of serious adverse effects. After administration of the intravenous infusion, about 18% of bisphosphonate-naïve patients experience an acute-phase reaction, including low-grade temperature, aches, and pains. This is reduced to about 9% in those who have been treated with oral bisphosphonates, and is further reduced by the concomitant and subsequent administration of acetaminophen. The likelihood and magnitude of the acute-phase reaction is less after the second infusion. Other adverse effects are similar to those encountered with other bisphosphonates. Because it is mostly excreted by the kidneys, zoledronic acid should not be administered to patients with a creatinine clearance less than 35 mL/min. It should not be administered to patients with hypocalcemia.Keywords: zoledronic acid, zoledronate, osteoporosis, osteopenia, bisphosphonates